6 - Peer-review and the Electronic Journal: Opportunities for the participation of developing countries’ scientists in mainstream science - Williams Nwagwu (Africa Media Review, 2006)
This paper traces the origin and evolution of the peer review process, highlighting its strengths and weaknesses to date. The author suggests that technology offers new opportunities for automated non-blinded open review process in which the identities of the author and the reviewer are not shielded. This approach, the author argues, conforms with the openness culture of the Internet. Options and strategies for effecting this type of review process are suggested.